Assessment of Adenosine Deaminase Level and the Utility of Polymerase Chain Reaction in Diagnosis of Tuberculous Pleural Effusion - Nagila, A; Khanal, S; Dhakal, N; Bhatta, M; Tamrakar, B K (Journal of Gandaki Medical College-Nepal, 2018)
Background: Extrapulmonary tuberculosis is one of the major causes of exudative pleural effusion. The paucibacillary nature of effusion suggests the need of markers and methodologies for accurate diagnosis and prognosis of tuberculosis as well as to differentiate it from other non-tubercular causes of pleural effusion.Objectives: This study was focused to evaluate the utility of polymerase chain reaction (PCR) in detection of tuberculosis antigen and to assess the level of Adenosine Deaminase (ADA) in tubercular pleural effusion (TPE) and contrast it with other causes.Methods: This is a cross-sectional study where 100 samples of pleural effusion suspected to be tuberculosis were analyzed by PCR for the detection of IS6110 segment of DNA. The level of ADA was then determined and compared in both PCR positive and negative samples. The cut-off value of ADA was >40 U/L for TPE. Student t test was applied to compare the means with statistical significance set at p40 U/L) in 43% TPE samples whereas all the non-tuberculosis effusion had ADA